Competing with Crohn's disease - Ng, V. K.; Millard, W. M. (The Physician and Sportsmedicine, 2005)
Crohn's disease is a chronic inflammatory bowel disorder that has genetic and environmental risk factors. Although moderate physical activity seems to reduce the risk of developing Crohn's disease, some high-performance athletes live with the disease. Uncontrolled Crohn's disease predisposes patients to numerous nutrient deficiencies and associated health issues such as anemia and osteoporosis. Low-intensity exercise has been shown to decrease flare-ups in sedentary patients; however, high-intensity exercise may lead to increased symptoms. Physicians play a crucial role in coordinating a team approach among the athlete, parents, coach, and athletic trainers to provide the best possible management of diet, training schedule, and treatment.